2010
DOI: 10.1080/19401491003615669
|View full text |Cite
|
Sign up to set email alerts
|

Coupling a model of human thermoregulation with computational fluid dynamics for predicting human–environment interaction

Abstract: Coupling a model of human thermoregulation with computational fluid dynamics for predicting humanenvironment interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…As the UTCI may be coupled easily to measurements from meteorological monitoring stations (Spagnolo and de Dear 2003) or to computational fluid dynamics software (CFD) simulating the physical parameters of the thermal environment (Cropper et al 2010), our results suggest that the UTCI may serve as a suitable planning tool for urban thermal comfort in sub-tropical regions.…”
Section: Discussionmentioning
confidence: 97%
“…As the UTCI may be coupled easily to measurements from meteorological monitoring stations (Spagnolo and de Dear 2003) or to computational fluid dynamics software (CFD) simulating the physical parameters of the thermal environment (Cropper et al 2010), our results suggest that the UTCI may serve as a suitable planning tool for urban thermal comfort in sub-tropical regions.…”
Section: Discussionmentioning
confidence: 97%
“…The results demonstrated that Venetian blinds could enhance the buoyancy-driven natural ventilation of the facade cavity. Cropper et al (2010) developed a CFD model to simulate the airflow and temperatures around human body using the shear stress transport (SST) k − ω model (Menter 1994). This model was further coupled with a thermal comfort model, which was able to predict human thermal comfort in various environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A CFD study for PV integrated with a transient bio-heat model included the computation of segmental skin temperatures, overall thermal sensation, and overall thermal comfort [113]. In addition to PV studies, coupling CFD and a human-body thermoregulation model has been extensively employed in common studies in indoor environments [147,155,156,161,167,168].…”
Section: Coupling Of Cfd and Thermoregulation Modelsmentioning
confidence: 99%